Reality Bias of "Return (Kembali)" for Recidivists in the Film "Pulang" (Semiotic Analysis of John Fiske) - Robin, Patricia; Giancinta, Stefany (Jurnal Multidisiplin Madani, 2024)
Film is an effective art medium in conveying ideas, but it cannot be separated from the subjective interpretation of the audience. This research discusses the film "Pulang" by PT Kereta Api Indonesia, which focuses on the element of bias over the meaning of the word "Return (kembali)" for the recidivist as the central character. The research team used John Fiske's Semiotics to help explore the complex layers of meaning in this film. Qualitative research methods and a critical paradigm approach were used to understand the subject contextually and avoid right or wrong judgements. Critical analysis highlights the social dynamics involved in the production and reproduction of meaning. In the film itself, the concept of "going home" does not simply mean returning to one's place of origin, but also includes the process in which the character regains acceptance from his family